Costas Montis a Cypriot Poet (1914 -2004) - Papaleontiou, Eleftherios (Études helléniques / Hellenic Studies, 2006)
Costas Montis cultivated poetry, particularly short poems, but he also wrote prose and, to a lesser extent, theatre, revue and translation. His poetic output is defined mainly by Moments, a series of short poems that he published in 1958 and that have been supplemented up to 2002, and by the trilogy Grammata sti mitera / Letters to Mother, three «complex» poems in which the poetic nuclei of his Moments are developed. Political problems, existential anxieties, mental changes and remarks about himself are conveyed in an abstract way, sometimes with humour and sarcasm and sometimes with bitter satire or limpid irony. They are summed up in concise poems that are short, sometimes even a single line.